Constant Bit Rate For Video Streaming Over Packet Switching Networks - Nasser N. Khamiss; Hamsa A. Abdullah (مجلة النهرين للعلوم الهندسية, 2008)
This paper proposed a technique of bit-rate control for video streaming over constant bit-rate communication channel, where the MPEG-2, standard variable bit-rate (VBR), is adapted to be used as a constant bitrate (CBR). The target image quality and output rate of the video encoder is controlled by feedback based on the buffer level. A CBR transport over networks, result is a good performance compared with that of VBR. It introduced simplicity of network monitoring